Chemically induced behavioral responses in Anopheles minimus and Anopheles harrisoni in Thailand - Rungarun Tisgratog (2018)
Behavioral responses of female mosquitoes representing two species in the Minimus Complex exposed to an operational field dose of bifenthrin or DEET (N,N-diethyl-m-toluamide) were described using an excito-repellency test system. Two test populations of An. minimus, one from the field (Tak Province, western Thailand), the other from a long-established laboratory colony, and Anopheles harrisoni collected from Kanchanaburi Province, western Thailand, were used. Results showed that all test populations rapidly escaped after direct contact with surfaces treated with either bifenthrin or DEET compared to match-paired untreated controls. Greater escape response by exposed females to bifenthrin and DEET were observed in the An. minimus colony compared to the two field populations. Field-collected An. minimus demonstrated a more rapid escape response to DEET than to bifenthrin, whereas An. harrisoni showed a converse response. Although fewer females escaped from test chambers without direct contact with treated surfaces compared to contact tests, the spatial repellency response was significantly pronounced in all test populations compared to match-paired controls (P < 0.05). DEET was found to perform as both a contact stimulant and moderate spatial repellent. © 2011 The Society for Vector Ecology.